Antivaccine, denialist, and conspiracy theorist content on Facebook. An analysis of the No to the New World Order page - Julio C. Aguila Sanchez; Carmen Castillo Rocha; Ángel R. Vargas Valencia (Information Research: An International Electronic Journal)
Introduction. Antivaccine, denialist, and conspiracy ideas are generally part of an ecosystem of beliefs reinforcing each other. With the advent of covid-19, these ideas figure among the main disinformation contents of counter-official discourses. The article aims to characterize the contents of the Facebook page ‘No to the New World Order’.